2011
DOI: 10.1136/gutjnl-2011-301095
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of inflammatory bowel disease in women with endometriosis: a nationwide Danish cohort study

Abstract: The risk of IBD in women with endometriosis was increased even in the long term, hence suggesting a genuine association between the diseases, which may either reflect common immunological features or an impact of endometriosis treatment with oral contraceptives on risk of IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 21 publications
1
80
1
4
Order By: Relevance
“…In addition, the risk was not explained by the recently suggested association between endometriosis and risk of CD 29. Oral contraceptives were also associated with a modest, but non-significant increase in risk of UC.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, the risk was not explained by the recently suggested association between endometriosis and risk of CD 29. Oral contraceptives were also associated with a modest, but non-significant increase in risk of UC.…”
Section: Discussionmentioning
confidence: 64%
“…In fact, immune deficits fulfilling most of the basic criteria for autoimmune disease have been described in endometriosis, including polyclonal B-cell activation, abnormalities in T- and B-cell function, tissue damage, and multi-organ involvement [38,39]. Furthermore, allergies, hypothyroidism, inflammatory bowel disease, and fibromyalgia are among a number of autoimmune conditions known to be associated with endometriosis [40,41]. However; it remains unclear whether these comorbidities may be a cause or an effect of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Guadagno et al investigated the histological correlation between CD and endometriosis and concluded that in women with known endometriosis histological IBD-like lesions, such as crypt distortion and mucosal surface alteration, should be considered as an epiphenomenon of endometriosis, not as a true IBD [18]. A Danish study demonstrated an increased risk of developing IBD among a large cohort of 37661 women with endometriosis and the risk was higher in women who had endometriosis verified by surgery [19]. The authors speculated that this association may be explained by shared immunological features between endometriosis and IBD or it may reflect a consequence of endometriosis treatment (in particular the oral contraceptives).…”
Section: Discussionmentioning
confidence: 99%